Magnetic epoxy nanocomposites reinforced with hierarchical α-Fe2O3 nanoflowers: a study of mechanical properties. (28th September 2017) - Balguri, Praveen Kumar; Harris Samuel, D G; Thumu, Udayabhaskararao
Abstract: In this work, we presented the potentiality of monodispersed 3D hierarchical α -Fe2 O3 nanoflowers ( α -Fe2 O3 ) as reinforcement for epoxy polymer. α -Fe2 O3 are synthesized through the thermal decomposition of iron alkoxide precursor in ethylene glycol. α -Fe2 O3 /epoxy nanocomposites (0.1 wt% of α -Fe2 O3 ) show 109%, 59%, 13%, and 15% enhancement in impact (un-notched), impact (notched), flexural and tensile properties, respectively. The uniformly embedded α - Fe2 O3 nanoflowers in epoxy polymer not only provide mechanical strength but also induced magnetic nature to the nanocomposite as observed from the Scanning electron microscopy and vibrating sample magnetometer.